2014
DOI: 10.1007/s00270-014-0973-3
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Lumen Chest Port Infection Rates in Patients with Head and Neck Cancer

Abstract: HNC patients are at increased risk for infection of dual-lumen chest ports placed via a jugular approach compared to patients with other malignancies. Tracheostomy is associated with infection in HNC patients but is not an independent risk factor for infection in the oncologic population as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Especially with dual lumed chest ports placed via a jugular approach, patients with head and neck cancer experience significantly more infections (42 vs 30), an increased infection rate per 1000 catheter days (0.68 vs 0.21), and more early infections within 30 days than patients with non‐head and neck cancer (10 vs 6). Moreover, an existing tracheostomy at the time of port placement is associated with infection in this setting of patients but not in the study population overall …”
Section: Discussionmentioning
confidence: 80%
“…Especially with dual lumed chest ports placed via a jugular approach, patients with head and neck cancer experience significantly more infections (42 vs 30), an increased infection rate per 1000 catheter days (0.68 vs 0.21), and more early infections within 30 days than patients with non‐head and neck cancer (10 vs 6). Moreover, an existing tracheostomy at the time of port placement is associated with infection in this setting of patients but not in the study population overall …”
Section: Discussionmentioning
confidence: 80%
“…Bos et al 19 recently reported an increased rate of port infection in patients with HNC compared with nonHNC (0.68 per 1000 catheter days vs. 0.21 per 1000 catheter days, respectively, p < 0.001). In the current study, the rate of infection for HNC patients was similar (0.53 per 1000 catheter days).…”
Section: Discussionmentioning
confidence: 94%
“…In accordance with this result, the number of sessions for the device placements was not a variable affecting overall device infections in multivariate regression analyses ( p = 0.82). Overall port infection rates in patients with HNC are reported to be higher, ranging between 5.8% and 8.5%, 10 12 possibly related to local radiotherapy and tracheostomy 13 , 14 compared to the infection rates reported in general cancer population ranging between 0.7% and 1.1%. 15 17 The early port infection rates in the single-session group (3.0%) and two-session group (4.0%) are similar to the rate reported by Bos et al 12 who observed an early port infection rate of 3.3% in patients with HNC; this was significantly higher compared to the rate of 1.3% in their control group with non-HNC.…”
Section: Discussionmentioning
confidence: 93%
“…A breach in sterile technique during port placement has been attributed as a cause of early port infections. 12 Inpatient placement, 16 neutropenia, 15 and serum albumin at the time of placement 8 have also been reported to be risk factors for early port infections. Among these risk factors, inpatient placement ( p = 0.01) was significantly more common and serum albumin at the time of device placement ( p = 0.04) was significantly lower in two-session group, indicating that the two-session group may include more infirm patients than the single-session group.…”
Section: Discussionmentioning
confidence: 99%